Sports analytics: maximizing precision in predicting MLB base hits - Alceo, Pedro Miguel Gonçalves André (2020)
Dissertation presented as the partial requirement for obtaining a Master's degree in Information Management, specialization in Knowledge Management and Business Intelligence